2019
DOI: 10.3389/fimmu.2019.01870
|View full text |Cite
|
Sign up to set email alerts
|

The Human G Protein-Coupled ATP Receptor P2Y11 Is Associated With IL-10 Driven Macrophage Differentiation

Abstract: The G protein-coupled P2Y 11 receptor is known to sense extracellular ATP during inflammatory and immune responses. The dinucleotide NAD + has also been proposed to be a P2Y 11 receptor ligand but its role is less clear. Here, we have examined for the first time human P2Y 11 receptor protein levels and show that the receptor was upregulated during polarization of M2 macrophages. IL-10 reinforced P2Y 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 49 publications
1
45
0
Order By: Relevance
“…While IL-1 receptor signalling was enhanced, TLR4 responses appeared to be suppressed. We have recently shown that P2Y 11 receptor-driven IL-8 secretion requires IKK and ERK as critical signalling components, both in the ectopic expression system and in primary human M2 macrophages (Gruenbacher et al, 2019). Our current observation that P2Y 11 receptors engage the IL-1 receptor signalling is in accordance with our previous findings, because IL-1 receptor responses likewise depend on IKK and ERK ( Figure S1) (Weber et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…While IL-1 receptor signalling was enhanced, TLR4 responses appeared to be suppressed. We have recently shown that P2Y 11 receptor-driven IL-8 secretion requires IKK and ERK as critical signalling components, both in the ectopic expression system and in primary human M2 macrophages (Gruenbacher et al, 2019). Our current observation that P2Y 11 receptors engage the IL-1 receptor signalling is in accordance with our previous findings, because IL-1 receptor responses likewise depend on IKK and ERK ( Figure S1) (Weber et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…We have previously shown that P2Y 11 receptor expression is upregulated during human M2 macrophage differentiation (Gruenbacher et al, 2019), suggesting that expression of these receptors contributes to the anti-inflammatory function of this macrophage subset. To extend these studies, we have now examined ectopic P2Y 11 receptors in a recombinant cell system and native P2Y 11 receptors in human monocyte-derived M2 macrophages.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The present data indicate that P2Y11R is linked to degranulation responses in LAD2 cells. This conclusion is based on (i) the expression of P2Y11 (Supplemental Figure 1), (ii) the lack of enhancing effect of purines and pyrimidines that target the other P2YR expressed by LAD2 cells, (iii) the strong enhancing effects of ATPγS, an agonist at the P2Y11R, [25][26][27] and (iv) the marked inhibition of ATPγS' effects by NF157, a selective P2Y11R antagonist. 28,29 Mechanistically, the P2Y11R effects involve the PI3K/Akt pathway but not the induction of intracellular Ca 2+ mobilization following WAS triggering.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, AMPK regulates nicotinamide phosphoribosyl transferase (NAMPT). NAMPT is the rate-limiting enzyme in the NAD+ salvage pathway and is associated with the activation of anti-inflammatory signaling (Audrito et al, 2015[ 2 ]; Gruenbacher et al, 2019[ 22 ]). IL-10 is an essential effector molecule of this process.…”
Section: Molecular Pathways Involved In the Macrophage Metabolic Reprogrammingmentioning
confidence: 99%